Antithrombotische Therapie bei akutem Koronarsyndrom und Vorhofflimmern - Darius, Harald (DMW - Deutsche Medizinische Wochenschrift, 2020)
The number of patients with atrial fibrillation (AF) is increasing due to the aging of the population. In addition, the number of patients with AF and an indication for oral anticoagulation (OAC) for the prevention of strokes increases, who are in need for a dual antiplatelet therapy (DAPT) with acetyl salicylic acid (ASA) plus a P2Y12-Inhibitor because of an acute coronary syndrome and/or coronary stent implantation. These patients did receive a triple therapy (TT) for 3–12 months in the past. Triple therapy never has been studied for efficacy or safety, however, the rate of bleeding complications in comparison to OAC or DAPT is significantly higher.Registries and smaller trials showed that dual therapy with an OAC plus a single platelet inhibitor may be sufficient to prevent strokes and stent thromboses/myocardial infarctions. Four prospective randomized trials involving all four NOACs (Non-Vitamin K oral anticoagulants) approved for stroke prevention in AF have been undertaken. The NOACs plus one antiplatelet agent were tested versus vitamin K-antagonists plus DAPT. In the meantime, the trials involving rivaroxaban (PIONEER AF-PCI), dabigatran (RE-DUAL PCI), apixaban (AUGUSTUS), and edoxaban (ENTRUST-AF-PCI) have been published. The current status is that a NOAC plus a single antiplatelet agent, mostly clopidogrel, is superior to TT with respect to the bleeding complications, without any obvious and statistically significant disadvantage for stroke rates or cardiac ischemic events. The international guidelines already recommend to treat with a NOAC and one antiplatelet agent instead of TT in case the patients bleeding risk is prevailing. Thus, TT seems not to be indicated anymore for most patients with AF and ACS or PCI.
Keywords: Antikoagulation; Vorhofflimmern; PCI; akutes Koronarsyndrom; Thrombozytenhemmer